Are Preoperative CT Findings Useful in Predicting the Duration of Laparoscopic Appendectomy in Pediatric Patients? A Single Center Study - Taskent, Ismail; Ece, Bunyamin; Narsat, Mehmet Ali (MDPI AG, 2024)
Background/Objectives: Preoperative computed tomography (CT) imaging plays a vital role in accurately diagnosing acute appendicitis and assessing the severity of the condition, as well as the complexity of the surgical procedure. CT imaging provides detailed information on the anatomical and pathological aspects of appendicitis, allowing surgeons to anticipate technical challenges and select the most appropriate surgical approach. This retrospective study aimed to investigate the correlation between preoperative CT findings and the duration of laparoscopic appendectomy (LA) in pediatric patients. Methods: This retrospective study included 104 pediatric patients diagnosed with acute appendicitis via contrast-enhanced CT who subsequently underwent laparoscopic appendectomy (LA) between November 2021 and February 2024. CT images were meticulously reviewed by two experienced radiologists blinded to the clinical and surgical outcomes. The severity of appendicitis was evaluated using a five-point scale based on the presence of periappendiceal fat, fluid, extraluminal air, and abscesses. Results: The average operation time was 51.1 ± 21.6 min. Correlation analysis revealed significant positive associations between operation time and neutrophil count (p = 0.014), C-reactive protein levels (p = 0.002), symptom-to-operation time (p = 0.004), and appendix diameter (p = 0.017). The total CT score also showed a significant correlation with operation time (p < 0.001). Multiple regression analysis demonstrated that a symptom duration of more than 2 days (p = 0.047), time from CT to surgery (p = 0.039), and the presence of a periappendiceal abscess (p = 0.005) were independent predictors of prolonged operation time. In the perforated appendicitis group, the presence of a periappendiceal abscess on CT was significantly associated with prolonged operation time (p = 0.020). In the non-perforated group, the presence of periappendiceal fluid was significantly related to longer operation times (p = 0.026). Conclusions: In our study, preoperative CT findings, particularly the presence of a periappendiceal abscess, were significantly associated with prolonged operation times in pediatric patients undergoing laparoscopic appendectomy. Elevated CRP levels, the time between CT imaging and surgery, and a symptom duration of more than 2 days were also found to significantly impact the procedure’s duration.
Keywords: Article